Change your mind: Stevonnie's new body schema and queer literacies in Steven Universe. Issue 3 (2nd October 2021) - Kennedy, Fen
Abstract: Queer media is a vital tool for building empathetic and much needed relationships across communities of multiple sex and gender identities. In this article I use visual analysis to illustrate how the children's TV series Steven Universe, and specifically the character design of Stevonnie, elucidate non-binary identity and humanity. Stevonnie emerges from a queer-analogous process called 'fusion'—specifically the fusion of a cis-male, part alien boy and his cis -female human best friend, producing a non-binary identity from the fact of their internal multiplicity. Through Stevonnie's character design, their introduction, their relationships, and their interaction with sexing and sexuality, the series offers young viewers an expanded understanding of the body's potential—to differentiate sex and gender, and to consider sex and gender as multiple within the same individual human existence. Series creator Rebecca Sugar used visual strategies as an important tool for communicating complex emotional concepts without provoking censorship, and to give Stevonnie a rich and empathetic appeal that moves beyond oppressive stereotyping of non-binary identities.